Challenges and Choices: Modelling New Zealand's Long-term Fiscal Position - Matthew Bell; Gary Blick; Oscar Parkyn; Paul Rodway; Polly Vowles (New Zealand Government, The Treasury, 2010)
This working paper provides further detail on the modelling behind Challenges and Choices – New Zealand's Long-Term Fiscal Statement, published on 29 October 2009. Building on the first Statement of 2006, we construct two main fiscal scenarios over a 40- year horizon. The historic trends scenario allows historic and current spending and revenue settings to interact with changing demography. The sustainable debt scenario applies a fiscal constraint on non-benefit spending so that Crown net debt follows the Government's medium-term fiscal targets. The modelling innovations introduced this time do not alter the basic structure and principles of the Long-term Fiscal Model, but instead provide insights into government spending: public sector productivity growth and the growth of the basket of services each person receives. These innovations enable us to illustrate the effects of tradeoffs between broad spending categories in a constrained fiscal environment. In the 2009 Statement, these policy changes are combined into three possible scenarios for obtaining a sustainable fiscal position. The paper also illustrates the sensitivity of the fiscal position to small changes in the demographic, macroeconomic and fiscal modelling assumptions.
Keywords: E62; H50; H68; J11; 330; Population; projections; social expenditure; fiscal costs; New Zealand; Finanzpolitik; Bevölkerungsentwicklung; Öffentliche Sozialausgaben; Neuseeland